Preferences on Investing in Malaysian Stocks and Futures Markets - Hooi Hooi Lean, (Kajian Malaysia, 2015)
This paper investigates the preference of spot and futures markets in Malaysia for risk averters and risk seekers. The stochastic dominance approach is employed to perform the empirical analysis. It is observed that spot is preferred to futures at the downside risk whereas futures is preferred to spot at the upside profits for the entire period as well as all sub-periods. Spot dominates futures for risk averters while futures dominate spot for risk seekers. The preference of spot and futures markets for both risk averters and risk seekers are robust to crisis. In addition, the results support efficiency of both markets. In addition, several positive measures imposed by the government play a big role in stabilising the economy and sustain financial markets.